Changes to human faecal microbiota after international travel. Issue 44 (November 2021) - Kampmann, Christian; Dicksved, Johan; Engstrand, Lars; Rautelin, Hilpi
Abstract: Background: The aim was to investigate whether travelling to less-resourced destinations influences the composition of faecal microbiota in generally healthy adults. Method: In this prospective observational study, 47 adults (median age, 24 years; 73% females) travelled from Sweden to distant destinations for 1–12 weeks. Five faecal samples, two before and three after travel, were analysed by 16S amplicon massive parallel sequencing. Subjects had taken no antibiotics within three months of each sampling. Results: The overall composition of faecal microbiota was not affected by travel. However, when looking at the relative abundance of individual bacterial taxa, Enterobacteriaceae demonstrated a 10-fold increase immediately after the trip as compared to the samples taken before travelling. Conversely, the relative abundance of Christensenellaceae had decreased equally much. Both these changes were reversible within nine weeks. Conclusions: International travel, even to less-resourced countries, did not appear to alter the overall diversity of human faecal microbiota as studied here after travelling. However, Enterobacteriaceae bacteria, often associated with infection, inflammation, and antibiotic resistance, showed dramatically elevated levels, and Christensenellaceae, frequently associated with healthy conditions, demonstrated remarkably declined levels in relative abundance as detected immediately after travel. Both these changes returned to original pre-travel levels within nine weeks.